SYNTACTIC AND PRAGMATIC FEATURES OF ENGLISH TAG QUESTION / Lê Thị Tố Uyên; NHDKH Assoc.Prof.Dr Vo Dai Quang - Lê, Thị Tố Uyên
In English, tag questions play an important part in communicative process. People are not able to communicate well without making and answering questions. In reality, people make tag question for confirmation or checking information. It is obvious that tag questions cannot be missed in communication. However, there are several problems when using tag questions. Therefore, the purpose of this study is to describe the syntactic and pragmatic features of English tag questions. This study used both quantitative and qualitative methods as the main ones. In addition, a descriptive method was also used to shed light into the features of these English structures in terms of syntax and pragmatic. Finally, some other methods and techniques such as statistical technique and error method were also used by the writer of this paper to measure the chosen participants’ ability to respond to a written test and an oral test. In the previous research, the syntactic and pragmatic features were shown. However, this study’s contributions are: describing the syntactic and pragmatic features of English tag question and pointing out the commonly errors committed by students at Nguyen Thi Minh Khai high school and the solutions to the errors will be recommended. These findings will be useful.